Grit and Foreign Language Anxiety as Predictors of Willingness to Communicate in the Context of Foreign Language Learning: A Structural Equation Modeling Approach - Jalil Fathi; Farnoosh Mohammaddokht; Saeed Nourzadeh (Issues in Language Teaching, 2021)
Given its key role in enhancing learners’ communicative competence, willingness to communicate (WTC) has received much research attention in the field of second language (L2) teaching and learning. Numerous studies have explored the antecedents of WTC in English as a Foreign Language (EFL) context. As an attempt to shed more light on this line of research, this study was set to investigate the effects of grit and foreign language anxiety as predictors of L2 WTC among Iranian EFL learners. For this purpose, a number of 163 undergraduate English major students from several universities participated in this survey. The required data were collected by distributing valid and reliable instruments measuring the three target variables (i.e., WTC, grit, and anxiety). A structural equation modeling (SEM) approach was utilized to test the hypothesized structural models for the relations between these variables. The SEM results indicated that grit accounted for 10.6 % of the variance and FL anxiety explained 20% of the variance in the participants’ L2 WTC. Furthermore, the unique impact of foreign language anxiety on WTC was greater than that of grit. The implications of these findings for language teaching and learning are discussed at the end of the paper.